Bilangan Kromatik Grap Commuting dan Non Commuting Grup Dihedral - Rahayuningtyas, Handrini; Abdussakir, Abdussakir; Nashichuddin, Achmad (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2015)
Commuting graph is a graph that has a set of points X and two different vertices to be connected directly if each commutative in G. Let G non abelian group and Z(G) is a center of G. Noncommuting graph is a graph which the the vertex is a set of G(G) and two vertices x and y are adjacent if and only if xyâ‰ yx. The vertex colouring of G is giving k colour at the vertex, two vertices that are adjacent not given the same colour. Edge colouring of G is two edges that have common vertex are coloured with different colour. The smallest number k so that a graph can be coloured by assigning k colours to the vertex and edge called chromatic number. In this article, it is available the general formula of chromatic number of commuting and noncommuting graph of dihedral group